2012
DOI: 10.1364/oe.20.024642
|View full text |Cite
|
Sign up to set email alerts
|

Generation of isolated attosecond pulses of sub-atomic-time durations with multi-cycle chirped polarization gating pulses

Abstract: Abstract:We theoretically investigate the X-ray supercontinuum generated by interaction of multi-cycle, chirped polarization gating pulses with the helium gas. It is shown that with this scheme, an isolated sub-50-attosecond pulse can be obtained straightforwardly without any phase compensation. Interestingly, if one selects an extremely broad spectral range near the highorder harmonic cutoff, an isolated and intense sub-24-attosecond pulse can be generated after phase compensation, which could be used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…From the harmonic spectra shown in figures 4(c1)-(c3), one can see that besides the narrow super-continuum structure in the cutoff, a very broad quasi-continuum structure is also observed, as indicated by the double arrows. If there exists a certain relation between the harmonic phase and frequency for these broadband quasi-continuum spectra, then a broader spectral range can be selected to produce a shorter isolated attosecond pulse by applying phase compensation [23,36]. Hence, in the following, we perform a detailed phase analysis of the harmonics to find the broadest spectral range where the phase compensation can be implemented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the harmonic spectra shown in figures 4(c1)-(c3), one can see that besides the narrow super-continuum structure in the cutoff, a very broad quasi-continuum structure is also observed, as indicated by the double arrows. If there exists a certain relation between the harmonic phase and frequency for these broadband quasi-continuum spectra, then a broader spectral range can be selected to produce a shorter isolated attosecond pulse by applying phase compensation [23,36]. Hence, in the following, we perform a detailed phase analysis of the harmonics to find the broadest spectral range where the phase compensation can be implemented.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a few-cycle laser system in general is difficult to operate and maintain [18]. To improve the scheme for isolated attosecond pulse generation, researchers proposed polarization gating method [19][20][21][22][23] and two-color polarization gating method [24]. With the twocolor polarization gating method, the harmonic efficiency was improved [24].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying physics behind this phenomenon is that the chirp can effectively increase the optical cycle of the driving laser field, after the laser reverses its direction, the quasifreely electron experiences a longest time acceleration when returning to the parent ion and obtains much higher kinetic energy from the driving laser field; as a result, the cutoff position of HHG is extended significantly. Moreover, this approach also has the potential to select a short or long quantum path, which leads to the production of isolated short attosecond pulses, such as a 108-as pulse via an intense few-cycle chirped pulse, [25] a 10-as pulse with phase compensation using a chirped few-cycle laser and a static electric field, [26] a 37-as (57-as) pulse by an intense few-cycle chirped laser and a half cycle pulse (an ultraviolet attosecond pulse), [27,28] a 59-as pulse by a multicycle chirped pulse combined with a chirp-free pulse, [29] a 31-as (5-as) pulse without (with) phase compensation using a two-color laser pulse with the combined chirps, [30] a 102-as pulse with a multicycle chirped and chirp-free two-color field, [31] a sub-24-as pulse with phase compensation using multi-cycle chirped polarization gating pulses, [32] and an intense isolated sub-40-as pulse generation in pre-excited He-ionic medium with the use of a same-frequency laser field synthesis. [33] In our previous work, [34] by combining a 9-fs/800-nm fundamental chirped pulse and a 9-fs/1600-nm controlling chirped pulse, we realized a 1342-eV supercontinuum with a short path contribution and also obtained an isolated 28-as pulse with a bandwidth of 155 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent simulation calculation showed that a static electric field can not only modulate the quantum paths of the HHG, but also increase the ionization yield of electrons contributing to the continuous spectrum; as a result, the extension and enhancement of the HHG spectrum are achieved synchronously, which results in the production of an intense isolated 26-as pulse. [42] In this paper, the motivation of our simulation lies in the following considerations: first, though isolated attosecond pulse generations from the single chirped pulse, [25,43] the single chirped pulse or two-color laser in combination with a static electric field, [26,44] and two-color chirped pulse [28][29][30][31][32][33][34] have been investigated, few studies have been reported for the combination of the multicycle two-color chirped pulse and a static electric field; second, one of the current theoretical methods for producing single ultrashort attosecond pulses is by using the phase compensation for an achievable supercontinuum spectrum, which is not easy to achieve in an experiment; third, we intend to generate a single attosecond pulse with a duration below one atomic unit of time by straightforwardly filtering a large range of harmonics. Due to these ideas, in this paper we further investigate the HHG and isolated attosecond pulse generation of a model Ne atom in a multicycle two-color chirped laser and a static electric field.…”
Section: Introductionmentioning
confidence: 99%